Therapeutic community: concept and practice of experience in the sixties - Goulart, Maria Stella Brandão (Revista de Psicologia, 2014)
This article shares information about the concept of therapeutic community, from a high-profile experiment in the sixties in a psychiatric hospital in the city of Belo Horizonte, in Minas Gerais. The discussion arises from historical research entitled “Hospital Galba Velloso and the vicissitudes of history of psychiatric reform in the 60’s in Minas.” The methodology used in this research drew on oral sources and on the study of the hospital case sheets, setting an effort in the field of social psychology and history of psychology in order to contribute to the theme identified as the Brazilian Psychiatric Reform. Finally, it has been established the limitation of a traditional concept of asylum as a space or “locus” of therapeutic work. The hospital, on the other hand, has been indicated as a means of construction promoting a corporate psychiatry.